UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - SABINA, VINA; AFIFAH, WIWIK; FIKRI, SULTON (Jurnal Independent, 2022)
AbstractThe purpose of this research is to find out the Termination of Employment by analyzing it usingthe perspective of human rights. This study uses a normative juridical method. The approachused is the statutory approach. The result is that since the existence of the COVID-19 pandemicit has had a negative impact because it has affected the economy which has threatened the lifeof the nation and state, and not many countries in the world have been able to survive. Indonesiahas experienced imbalances in various fields and living arrangements, especially in theeconomic sector which has resulted in decreased income of economic actors and led toinequalities in society such as layoffs, due to the many losses experienced by companiesranging from operating restrictions, decreased income and even many companies or mediumto lower businesses that have experienced a decrease in income so that it can be said to bebankrupt. This resulted in the company being forced to lay off employees because they wereno longer able to pay employee wages. The large number of workers who are laid off or affectedby layoffs affects the increase in the number of unemployed in Indonesia. Even though thereare provisions regarding layoffs, many companies that lay off their employees do not provideseverance pay as stipulated. The problem is that mass layoffs without severance pay are a formof human rights violation.